Particularities of physical and mental injuries for Ukrainian-Russian war victims - Stebliuk, Vsevolod; Gan, Roman; Pronoza, Kate (Journal of Education, Health and Sport, 2016)
Stebliuk Vsevolod, Gan Roman, Pronoza Kateryna. Particularities of physical and mental injuries for Ukrainian-Russian war victims. Journal of Education, Health and Sport. 2016;6(4):458-465. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.50626 http://ojs.ukw.edu.pl/index.php/johs/article/view/3495 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.04.2016. Revised 25.04.2016. Accepted: 28.04.2016. Particularities of physical and mental injuries for Ukrainian-Russian war victims Vsevolod Stebliuk*, Roman Gan**, Kateryna Pronoza*** *Ukrainian Military Medical Academy **Ivano-Frankivsk National Medical University *** NGO ”Ukrainian Society of overcoming the consequences of traumatic events” Prof. Vsevolod Stebliuk*, Dr. Roman Gan, PhD**, Kateryna Pronoza*** *Ukrainian Military Medical Academy **Ivano-Frankivsk National Medical University *** NGO ”Ukrainian Society of overcoming the consequences of traumatic events” Abstracts V. Stebliuk, R.Gan, K.Pronoza. Particularities of physical and mental injuries for Ukrainian-Russian war victims. The study was conducted for researching statistics dates and clinical results of physical and mental consequences of wounds for veterans of Ukrainian-Russian war especially PTSD-symptoms. More than 50% of injuries are extremities combat trauma. Near 30% wounded soldiers have different cranial-cerebral injuries. Other areas usually injured not frequently. The first place in the structure of non-traumatic diseases has mental disorders (near 30% of cases). After then, most common diseases are cardiovascular system’s problems (18%), pulmonary diseases (10%, like as acute respiratory infections and pneumonias), digestive problems (10%). In structure of mental disorders prevalence the somatophorm disorders (18%) an acute stress reaction (15%). Post-traumatic stress disorder (PTSD) was diagnosed in 14,26% of cases Key words: combat trauma, acute stress reaction, posttraumatic stress disorder.